Assessing the relationship between risk assessment practices, risk control practices, quality risk management and construction project performance: an empirical study in Malaysian construction projects / Affiaine Ahmad - Ahmad, Affiaine (2013)
This study focuses on the relationship between the risk assessment practices (RAP), risk control practices (RCP), quality risk management (QRM) and construction project performance (CPP). This study is basically a measurement centers around the implementation of the project risk management (PRM) that includes the processes concerned with identifying, analyzing, and responding to project risk. Survey data gathered from 264 projects in G7 grade of contractors in Malaysia was used to assessing the relationships between the stated variables. The analysis were performed using rigorous statistical analysis of SPSS version 16 and AMOS program for structural equation modeling (SEM) techniques.Results show that RAP is observed to have a positive relationship on QRM, but no direct relationship on CPP.RCP has direct positive relationship to both QRM and CPP. Whereas QRM has a positive relationship on CPP. It fully mediates the relationship between RAP and CPP and partially mediates the relationship between RCP and CPP. RAP and RCP are positively correlated. RAP influence the choice of measures; and RCP encourage implementation of RAP. The study contributes to better understanding of implementation of risk management in project. This holds practical and managerial implications to increase the understanding of project risk management and its related performance measurement. In nutshell this study provide useful insights to project managers seeking to improve performance in their construction projects as well as that of the chains they belong to. Thus, the results of this study can make a good addition among the consultants to in-house management training material on construction project management and project risk management.